Web based applications for energy management system incorporated network reconfiguration using genetic algorithm / Wan Adnan Wan - Wan Chik, Wan Adnan (2006)
The Web Based Applications for Energy Management System in UiTM has established itself as a strong medium for distributed computing: a network user interface that is powerful and an independent platform. This research was involved with the development of Web Based Applications for Energy Management System for providing Web application system, Web monitoring System and Genetic algorithm Based Network Reconfiguration Technique for loss minimization in the UiTM Distribution System. Web Based Applications for Energy Management System can be broadly classified into three basic methods. The Web Monitoring System is a sort of information system in which during a certain time on a systematic way, data are being collected, handled, managed, analyzed and presented data from energy meter (33 ION™ ). The Web Application System program is designed for the client to configure a system (e.g calculates a load flow). The development on Web Application system uses An ActiveX technology approach. The Genetic Algorithm Based Network Reconfiguration Technique for loss minimization in the UiTM Distribution System is also proposed based on general combinatorial optimization algorithm. The development uses language Active Server Pages (ASP), HTML and C/C++. This program was tested on a Windows platform, which is a typical development environment for Web Based Applications for Energy Management System in UiTM. It provides access to UiTM’s personnel via Internet or Network UiTM. The results show that optimal configuration of 32 number of feeder or the substation in UiTM could provide loss minimization, reduces the active power loss in a power system at UiTM distribution network.